Towards a Glossary of Ethiopian Manuscript Culture and Practice - Alehegne, Mersha (Aethiopica, 2011)
The study is aimed at providing definitions for important terms that have specialized meaning in the Ethiopian manuscript culture. Terms related with lemmatized entry are also given under the same entry and marked as synonyms. The entries are arranged alphabetically following the Latin alphabetical order.